2011
DOI: 10.1007/s00421-011-2102-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the metabolic energy cost of overground and treadmill walking in older adults

Abstract: We assessed whether the metabolic energy cost of walking was higher when measured overground or on a treadmill in a population of healthy older adults. We also assessed the association between the two testing modes. Participants (n = 20, 14 men and 6 women aged between 65 and 83 years of age) were randomly divided into two groups. Half of them went through the overground-treadmill sequence while the other half did the opposite order. A familiarization visit was held for each participant prior to the actual tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 37 publications
5
46
1
Order By: Relevance
“…As walking speed increased (1.6–1.8 m/s) the energy cost again began to increase. This is comparable to Berryman et al ,21 who reported a similar energy cost pattern for their participants (healthy elderly aged 68.9±4.6 years) when walking on a treadmill at speeds ranging from 0.67–1.56 m/s and the optimal walking speed was 1.33 m/s. Furthermore, our results also suggest that at lower speeds (0.50–0.84 m/s), the energy cost of walking on a treadmill is greater than on the ground.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As walking speed increased (1.6–1.8 m/s) the energy cost again began to increase. This is comparable to Berryman et al ,21 who reported a similar energy cost pattern for their participants (healthy elderly aged 68.9±4.6 years) when walking on a treadmill at speeds ranging from 0.67–1.56 m/s and the optimal walking speed was 1.33 m/s. Furthermore, our results also suggest that at lower speeds (0.50–0.84 m/s), the energy cost of walking on a treadmill is greater than on the ground.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, our results also suggest that at lower speeds (0.50–0.84 m/s), the energy cost of walking on a treadmill is greater than on the ground. Berryman et al 21 also showed that there was greater energy cost of treadmill walking compared with ground walking at all the speeds they tested. The reason for the increased energy cost may be due to a greater need for stabilisation via muscular contraction while treadmill walking than when walking on the ground 21…”
Section: Discussionmentioning
confidence: 90%
“…To our knowledge, this is the first study to compare the energy cost of overground vs. treadmill walking in PD patients. Our results are in line with previous studies conducted in healthy elderly subjects (15, 16). In our study, the higher metabolic cost on the treadmill is unlikely to be due to changes in the kinematics parameters since these did not differ between the overground and treadmill walking conditions.…”
Section: Discussionsupporting
confidence: 94%
“…The MDC values may also be of use in interpreting changes in clinical populations who have not otherwise had test–retest reliability established, as it is unlikely that patient groups will demonstrate MDC values lower than those of healthy adults. However, the benchmarks established in this manuscript are most appropriate for use in interpreting data collected during treadmill walking because physiological gait performance for over-ground and treadmill walking may not be equivalent (Berryman et al, 2012). …”
Section: Discussionmentioning
confidence: 99%